IMPLEMENTASI PENDEKATAN DEEP LEARNING PADA PEMBELAJARAN IPAS MATERI CAHAYA DAN SIFATNYA DI KELAS V - Fita Ayu Dwi Wahyanti; Agung Nugroho (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This discussion outlines the application of deep learning to the study of Natural and Social Sciences (IPAS) specifically the topic of the properties of lightin the fifth-grade class at SD Negeri Kaliputih, while also examining the associated challenges and supporting factors. This qualitative study takes the form of a case study involving the school principal, the fifth-grade teacher, and the fifth-grade students. Data were gathered through documentation, observation, and interviews, and subsequently analyzed using technique and source triangulation. The findings indicate that deep learning was implemented across several phases: lesson planning, execution, and evaluation. During the planning phase, the teacher developed student worksheets, instructional media, teaching modules, and assessment indicators aligned with the principles of meaningful, joyful, and mindful learning. The discussion further addresses the implementation, comprehension, and reflection aspects of the process. Evaluation was carried out through observation, presentation, reflection, and Wordwall-based quizzes. Supporting factors included school institutional support, teacher competence, student motivation, and adequate facilities and infrastructure. Inhibiting factors included differences in learning styles, time constraints, technological limitations, and student heterogeneity. It is concluded that the implementation of deep learning is capable of creating active, meaningful, and enjoyable learning experiences for students.